Interprofessional collaboration on mothers with perinatal mental health problems and disorders: A scoping review - Enggar Avilia Pragastiwi; Cesa Septiana Pratiwi (Universitas Aisyah Pringsewu, 2023)
Perinatal mental health problem and disorder often occurs in women during pregnancy and two year postpartum. Types of perinatal mental health problems and disordes include perinatal depression, post-traumatic stress disorder, postpartum psychosis, postpartum blues, and postpartum depression. Treatment and care for mothers with perinatal mental health problems need to be well-coordinated by skilled interprofessional teams that work collaboratively. This study aims to mapping out scientific evidence based on published articles on interprofessional collaboration among mothers with perinatal mental health issues and disorders. This study used PRISMA-ScR with the PEO framework, three databases, and one grey literature. Articles were selected through Prisma Flowchart and Critical Appraisal using Joanna Briggs Institute (JBI) and Mixed Method Appraisal Tool (MMAT). The literature search identified 10 out of 2441 articles, data charting was carried out on the ten selected articles to insert several points such as the aim of the research, authors, methodology, location, number of articles, and results of the research. Research which focus on interprofessional collaboration in managing perinatal mental health problems is very limited. The authors suggest future studies undergo a more comprehensive assessment and continued with integrated management of perinatal mental health problems and disorders. Collaborative practice skills are crucial in the future to support perinatal women who suffer from psychosocial pressures. Abstrak: Kesehatan mental perinatal adalah gangguan kejiwaan yang lazim terjadi pada wanita selama masa kehamilan dan selama 1 tahun setelah melahirkan. Jenis masalah Kesehatan mental perinatal seperti depresi kehamilan, post traumatic stress disorder, postpartum psikosis, postpartum blues, postpartum depression. Perawatan dan pelayanan ibu dengan gangguan kesehatan mental perinatal perlu dikoordinasikan dengan baik oleh tim interprofessional yang terampil dalam bekerja secara kolaboratif. Penelitian ini bertujuan untuk memetakan bukti ilmiah berdasarkan artikel yang telah diterbitkan terkait Interprofessional collaboration pada ibu dengan masalah dan gangguan mental perinatal. Penelitian ini mengguanakan PRISMA-ScR dengan frame work PEO, 3 data base dan 1 grey literatur, artikel diseleksi melalui Prisma Flowchart dan Critical Appraisal menggunakan Joanna Briggs Institute (JBI) dan Mixed Method Appraisal Tool (MMAT). Ditemukan 10 dari 2441 artikel, kemudian dilakukan charting data untuk memasukkan beberapa poin seperti tujuan penelitian, penulis, metodologi, lokasi, jumlah sampel dan hasil penemuan dari penelitian. Penelitian yang berfokus pada kolaborasi interprofessional dalam mengelola masalah kesehatan mental perinatal sangat terbatas. Penulis merekomendasikan agar studi penelitian selanjutnya melakukan penilaian dan tatalaksana yang lebih komprehensif serta holistik. Keterampilan praktik kolaboratif sangat diperlukan dimasa depan guna mendukung wanita perinatal yang mengalami tekanan psikososial.